Професійний стаж як чинник зміни ставлення працівників до органів внутрішніх справ своєї кар'єри - Мілорадова, Наталя Едуардівна (НТУ "ХПІ", 2010)
The article shows the results of studying of specific features of attitude of domestic affairs` employees to their career. It also tells about their career orientations and changes in these orientations depending on experience.
Keywords: специфіка діяльності; кар'єра; стаж; ставлення до кар'єри